Bahasa Indonesia (Bahasa Perjuangan Bangsa 1908-1938) - Dwijaya, Gus (PERIODE: Jurnal Sejarah dan Pendidikan Sejarah, 2024)
Abstract: This research aims to determine the role of language, especially Indonesian as a tool to unite the nation and fight for Indonesia`s independence, starting from the beginning of the national movement at the beginning of the 19th century, the process of forming national awareness in society, the Youth Congress as the beginning of unity nation, the pledge of the youth oath in 1928, and the development of Indonesian as a National Language with the holding of the first Indonesian Language Congress in 1938. The method used is the historical method by Kuntowijoyo which consists of 5 stages including topic selection, source collection (heuristics), criticism source (verification), interpretation (interpretation), and writing (historiography). Results obtained. The results of this research found the fact that Indonesian was born from Malay which has become the Lingua Franca for the majority of society and has become a connecting language between islands in the archipelago. Youth figures who care about language development.